Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Lingual Suicidal-Oriented Word Embedding toward Suicide Prevention

Abstract: Early intervention for suicide risks with social media data has increasingly received great attention. Using a suicide dictionary created by mental health experts is one of the effective ways to detect suicidal ideation. However, little attention has been paid to validate whether and how the existing dictionaries for other languages (i.e., English and Chinese) can be used for predicting suicidal ideation for a low-resource language (i.e., Korean) where a knowledge-based suicide dictionary has not yet been deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Specifically, prior research showed that linguistic characteristics revealed in social media posts (Sawhney et al, 2020(Sawhney et al, , 2021a) could be linked to suicidal ideation. In particular, utilizing suicide dictionaries made by domain experts has been demonstrated as effective (Lv et al, 2015;Cao et al, 2019;Gaur et al, 2019;Lee et al, 2020), and such lexicon-based methods are known to be fast, explainable, and easy to implement (Kotelnikova et al, 2021;Razova et al, 2021). For example, Lv et al (2015) developed and validated that a Chinese suicide dictionary made by domain experts helps predict suicidality.…”
Section: Suicidality Assessment With Suicide Lexiconmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, prior research showed that linguistic characteristics revealed in social media posts (Sawhney et al, 2020(Sawhney et al, , 2021a) could be linked to suicidal ideation. In particular, utilizing suicide dictionaries made by domain experts has been demonstrated as effective (Lv et al, 2015;Cao et al, 2019;Gaur et al, 2019;Lee et al, 2020), and such lexicon-based methods are known to be fast, explainable, and easy to implement (Kotelnikova et al, 2021;Razova et al, 2021). For example, Lv et al (2015) developed and validated that a Chinese suicide dictionary made by domain experts helps predict suicidality.…”
Section: Suicidality Assessment With Suicide Lexiconmentioning
confidence: 99%
“…With the recent advancement of deep learning technologies, high-performing deep learning models have been proposed for accurately assessing suicidality (Sawhney et al, 2021a,b;Cao et al, 2020). In this way, incorporating a suicide dictionary into a deep learning model has received great attention (Cao et al, 2019;Lee et al, 2020). For example, Cao et al (2019) built suicide-oriented word embeddings to intensify the sensibility of suiciderelated lexicons and employed a two-layered attention mechanism.…”
Section: Suicidality Assessment With Suicide Lexiconmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while the prior work has revealed valuable insights into understanding the behavior of BD patients revealed on social media, little attention had been paid to developing a model that can predict the future suicidality of a BD patient. Although a few studies have proposed methods to identify the current risk of suicide in a given social media post [30,43,44], suicidal ideation can often quickly lead to an actual attempt, thereby making them ineffective in preventing suicide [9,10,41,52]; hence, exploring the BD's risk factors that can lead to suicide ideation for predicting future suicidality is crucial. Therefore, this paper aims to predict the future suicidality of BD patients based on their mood I've wanted to die since I was in 4th grade.…”
Section: Introductionmentioning
confidence: 99%